Sedimentary Petrographic Study of Tephra, Glacial and Aeolian Grains in a Quaternary Paleosol Sequence on Mount Kenya, East Africa William - Mahaney, William; Vortisch, Walter; Fecher, Klaus (Géographie physique et Quaternaire, 1988)
ABSTRACTTephra, aeolian and glacial grains in a lithostratigraphic-paleosol sequence on Mount Kenya were studied to determine if their pétrographie properties would provide evidence for different paleoenvironments over the period of - 100,000 to - 500,000 yr BP. Till containing high quantities of ferromagnetic minerals alternate in the sequence with aeolian sediments and tephras containing an abundance of volcanic glass, quartz, and feldspars with variable degrees of etching. Quartz, an allochthonous mineral on Mount Kenya, appears to have an aeolian origin followed by ice transport which produced glacially-crushed surfaces. A comparison of weathering products in the two paleosols leads to the conclusion that precipitation-drainage conditions were quite different during the formation of these inter-glacial paleosols.